2004
DOI: 10.1002/chin.200440117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiinflammatory Activity of Heterocyclic Indole Derivatives.

Abstract: type (III), (V) and (VII) are prepared and tested for their antiinflammatory activities. Compound (Va) shows the most potent activity. -(RANI, P.; SRIVASTAVA, V. K.; KUMAR*, A.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…All the compounds of this series showed promising anti-inflammatory activity. The most active compound of the series, 3-[1-Acetyl-5-(p-hydroxyphenyl)-2-pyrazolin-3-yl] indole 32 was found to be most potent, which had shown higher percent of inhibition of oedema, lower ulcerogenic liability, and acute toxicity than the standard drug phenylbutazone 57 .…”
Section: Fig 41a: Compound 41a 41b: Compound 41bmentioning
confidence: 99%
“…All the compounds of this series showed promising anti-inflammatory activity. The most active compound of the series, 3-[1-Acetyl-5-(p-hydroxyphenyl)-2-pyrazolin-3-yl] indole 32 was found to be most potent, which had shown higher percent of inhibition of oedema, lower ulcerogenic liability, and acute toxicity than the standard drug phenylbutazone 57 .…”
Section: Fig 41a: Compound 41a 41b: Compound 41bmentioning
confidence: 99%
“…Compounds having pharmacophore such as chloro, fluoro, and bromo groups have exhibited best anti-convulsants 11 , antiinflammatory 12 , anticancer 13 , antitubercular 14 , antibacterial activity 15 , antifungal 16 , and antihistaminic 17 . From the above discussions it may be concluded that the modifications in bis (indolyl) moiety displayed valuable biological activities and these modifications can be utilized to develop potentially active agents.…”
Section: Introductionmentioning
confidence: 99%
“…2-Pyrazoline derivatives have been reported to exhibit various pharmacological activities such as antimicrobial (Karthikeyan et al, 2007;Zitouni et al, 2005aZitouni et al, , 2005b, anti-inflammatory (Bansal et al, 2001;Barsoum et al, 2006;Rani et al, 2004), antihypertensive (Zitouni et al, 2000), antidepressant (Palaska et al, 1996), and monoamine oxidase inhibitory activities (Soni et al, 1987). Similarly, phenolic derivatives such as gallocatechin, epigallocatechin, and caffeic acid, besides their analogs that contain several hydroxy groups on the phenyl moiety, were found to exhibit various useful properties including radical scavenging (Yokozawa et al, 1998), antiviral (Okuda, 2005), antioxidant (Torres de Pinedo et al, 2007), anti-inflammatory (Nazir et al, 2007), antiatherosclerotic properties (Visioli et al, 1995), anti-cancer (Oh et al, 2001), heart protecting (Jang et al, 1997), and strong topoisomerase inhibiting activities (Abdel-Aziz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%